Option talk and risk communication with people with limited health literacy: A qualitative focus group study with key stakeholders - Romy Richter; Esther Giroldi; Maarten Jonkmans; Juliette Linskens; Jany Rademakers; Trudy van der Weijden; Jesse Jansen (PLoS ONE, 2025)
Purpose To explore stakeholders’ views on acceptable and feasible strategies for discussion of treatment options and risk communication with people with limited health literacy (LHL in the context of shared decision-making (SDM)). Methods This qualitative descriptive study used purposive sampling to conduct focus groups with stakeholders including experts in health literacy, SDM, or risk communication (RC); experienced General Practitioners (GPs); and individuals with LHL. Each session included a brief presentation defining SDM, option talk, and RC, followed by an introduction to various RC strategies and decision aids to facilitate discussion. Verbatim transcripts were analysed by two independent researchers using inductive and deductive content analysis. Results Five focus groups were conducted, involving experts (two FGs, n = 5 and n = 6), GPs (one FG, n = 8) and people with LHL (two FGs, 2x n = 3). Experts and GPs emphasised the need to tailor communication to the patient’s context and noted challenges in identifying patients with LHL. All participants highlighted the importance of using illustrations of treatment options (e.g., knee injections) to support the discussion of options. Views on the level of detail required for RC varied, with some GPs questioning whether RC was understandable to people with LHL. Most people with LHL preferred RC in natural frequencies and icon arrays but noted that RC can fan fear. GPs found contextualisation (e.g., comparing the probability of a treatment outcome with the probability of a car accident) a helpful strategy, but patients found it confusing. Decision aids were seen as supportive for RC. Overall, people with LHL preferred their doctor to discuss options face-face with them, using a layered step-by-step manner, adding details on RC as preferred by patients. Conclusion SDM for people with LHL benefits from a tailored, layered approach with visual aids. These strategies are potentially useful for all patients, but further research is needed to confirm this.